Nonequilibrium statistical operators for systems with finite lifetime - Ryazanov, V.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
A family of nonequilibrium statistical operators (NSO) is introduced which differ by the system lifetime distribution over which the quasiequilibrium (relevant) distribution is averaged. This changes the form of the source in the Liouville equation, as well as the expressions for the kinetic coefficients, average fluxes, and kinetic equations obtained with use of NSO. The difference from the Zubarev form of NSO is of the order of the reciprocal lifetime of a system.